Mechanisms of passive ion permeation through lipid bilayers: Insights from simulations - Tepper, Harald L. (2006)
Multi-State Empirical Valence Bond and classical Molecular Dynamics simulations were used to explore mechanisms for passive ion leakage through a dimyristoyl phosphatidylcholine (DMPC) lipid bilayer. In accordance with a previous study on proton leakage, it was found that the permeation mechanism must be a highly concerted one, in which ion, solvent and membrane coordinates are coupled. The presence of the ion itself significantly alters the response of those coordinates, suggesting that simulations of transmembrane water structures without explicit inclusion of the ionic solute are insufficient for elucidating transition mechanisms. The properties of H(+), Na(+), OH(-), and bare water molecules in the membrane interior were compared, both by biased sampling techniques and by constructing complete and unbiased transition paths. It was found that the anomalous difference in leakage rates between protons and other cations can be largely explained by charge delocalization effects, rather than the usual kinetic picture (Grotthuss hopping of the proton). Permeability differences between anions and cations through PC bilayers are correlated with suppression of favorable membrane breathing modes by cations.